PENGARUH RISIKO BISNIS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putra, Yudi Ramanda; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to test partially and simultaneously the influence of business risk and sales growth against the capital structure of the company's Property and Real Estate sector which is listed on the Indonesia Stock Exchange. Where independent variables in this study are business risk and sales growth and dependent variables are capital structures. This research uses secondary data in the form of corporate financial statements from 2011-2016 period. The data analysis in this study used simple, multiple linear regression, coefficient of determination, test-T and test-F, using SPSS 23 device programs. The results of the analysis showed that partial business risk variables (T-tests) affected the property and real estate corporate capital structure listed on the Indonesia Stock Exchange, partial sales growth variables (Test T) were not affect the capital structure of the property and real estate companies listed on the Indonesia Stock Exchange. Simultaneous results (test f) indicates the influence of business risk and sales growth of the capital structure of property and real estate companies listed on the Indonesia Stock Exchange. Keywords: Business risk, sales growth, capital structure